2020
DOI: 10.1007/jhep11(2020)001
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the event-activity dependence of ϒ(nS) relative production in proton-proton collisions at $$ \sqrt{s} $$ = 7 TeV

Abstract: The ratios of the production cross sections between the excited ϒ(2S) and ϒ(3S) mesons and the ϒ(1S) ground state, detected via their decay into two muons, are studied as a function of the number of charged particles in the event. The data are from proton-proton collisions at $$ \sqrt{s} $$ s = 7 TeV, corresponding to an integrated luminosity of 4.8 fb−1, collected with the CMS detector at the LHC. Evidence of a decrease in these ratios as a function of the particle multiplicity is observed, more pronounced… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…The observations reported here may share a common origin with the results reported in [10]. The CMS collaboration measured the production of Υ (nS) mesons at √ s = 7 GeV as a function of the charged particle multiplicity in the underlying event.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The observations reported here may share a common origin with the results reported in [10]. The CMS collaboration measured the production of Υ (nS) mesons at √ s = 7 GeV as a function of the charged particle multiplicity in the underlying event.…”
Section: Discussionsupporting
confidence: 83%
“…Various extensions of the transverse-mass scaling incorporate different assumptions and are capable of describing a broad variety of experimental data with impressive precision [8]. In this letter, a more qualitative approach is presented providing a plausible corollary to measurements of Υ mesons made by the CMS experiment in pp collisions [9,10]. CMS observed an intriguing correlation between the order of the Υ (nS)-meson state and the multiplicity of charged hadrons measured in the collision, and suggested that this may correspond to a suppression of the excited Υ (nS) states in pp collisions.…”
Section: Introductionmentioning
confidence: 99%
“…The most discussed explanations for the excited state quarkonium production modification with respect to the ground states are rescattering phenomena, either of partonic or hadronic nature [290,369,[520][521][522], as well as applying transport equation approaches [523,524] as employed in nucleus-nucleus collisions. In order to investigate these phenomena, ratios or self-normalized double ratios of different states have been measured in pp collisions as a function of a number of charged tracks in the event or forward energy deposition [525,526].…”
Section: Heavy-flavor and Jet Hadronizationmentioning
confidence: 99%
“…Therefore, ϒhadron correlation studies will be feasible within the LHCb experiment. Moreover, the CMS experiment is expected to register around 1.7 million of ϒ in the LHC Run 3 [59], providing another opportunity for ϒ-hadron femtoscopy.…”
Section: Prospects For J/ψ-hadron Femtoscopic Measurementsmentioning
confidence: 99%